Prevalence, sequence diversity, and amplification of an IS-associated enterotoxin gene, astA, in Escherichia coli - Ooka, Tadasuke; Arai, Sakura; Lee, Kenichi; Gotoh, Yasuhiro; Kubomura, Akiko; Imuta, Naoko; Hara-Kudo, Yukiko; Iyoda, Sunao; Hayashi, Tetsuya; Nishi, Junichiro (Frontiers in Microbiology, 2025)
IntroductionEnteroaggregative Escherichia coli heat-stable enterotoxin 1 (EAST1) encoded by the astA gene was first identified in an enteroaggregative E. coli strain isolated from a patient with persistent diarrhea. While astA-positive strains sometimes cause large food poisoning outbreaks, the significance of EAST1 as a virulence factor remains unclear. Additionally, although the prototype and seven variants of the astA gene have been identified, the biological significance of these genetic variations remains undefined. This study aimed to elucidate the characteristics of the A gene by investigating its distribution and sequence diversity within the evolutionary lineages of Escherichia coli.MethodsWe conducted PCR screening for the astA gene in 2,726 E. coli strains isolated from children with diarrhea in Kagoshima, Japan, and blastn search of the astA gene was conducted on 9,065 publicly available finished E. coli genomes. The astA gene identified were subjected to analysis of sequence variation and comparison of their flanking genomic regions. In addition, the phylogenetic distribution of astA gene variants in E. coli lineage was also investigated.Results and discussionThe results showed that 185 (6.8%) of the Kagoshima strains and 690 (7.6%) of the database strains had similar possession rates. We identified 31 sequence variations (four known and 27 new variants [V8-34]) which were widely distributed in the E. coli lineages. Detailed sequence analyses revealed that 31 of the 35 astA gene types are intact and encode 23 types of EAST1 peptides. Although all 35 types were associated with IS1414, only three (prototype, V30, and V31) of the 31 intact astA gene types were encoded in the intact IS1414. A notable number of prototype-bearing strains (43/146 strains) possessed multiple copies (two to 11 copies) of this type of astA gene, indicating that the amplification has predominantly occurred in the prototype, which was driven by IS1414 amplification. However, given that the IS1414 associated with V30 and V31 also remain structurally intact, it is plausible that similar amplification events may occur in these variants in the future. These results provide an important basis to investigate the virulence of the astA-positive strains and the role of EAST1 as a virulence factor.